Alunos da educação básica visitam à universidade: instrumento para a aprendizagem da educação ambiental na extensão - Aguiar, Silvia Camila da Costa [UNESP]; Caminhas, Ana Margarida Theodoro [UNESP]; Mendes, Natalia Serra [UNESP]; Araújo, Paola Eduarda de [UNESP]; Cascaldi, Alexia Morello da Silva [UNESP]; Ferreira, Marina [UNESP]; Malinowsky, Daniel Fernandes [UNESP]; Perez, Júlia da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work, we demonstrate the importance of activities given in university extension capable of promoting the learning of citizenship and environmental education. We emphasize, as well, two visits of 180 students of 6th student grade of a public school to the Faculty of Agricultural Sciences and Veterinary - FCAV - UNESP, which were generating such learning. We analyze the representations of agriculture and nature of these students generated and their interrelationships to carry out these inspections and the practice of environmental education. The dialogue and reflection on the importance of activities of this nature - able to bring the university and the community - have made the members of this extension project realized the possible connection between teaching, research and extension. This experience forms part of the extension project "Environmental Education, Agriculture and Food Security in Basic Education" (Cultivaeco Project) that is supported by Proex since 2009, with the acquisition of resources and scholarships.

Neste trabalho, demonstramos a importância de atividades dadas na extensão universitária capazes de promover a aprendizagem da cidadania e da educação ambiental. Destacamos, assim, duas visitas de 180 estudantes de 6ª. série de uma escola pública à Faculdade de Ciências Agrárias e Veterinárias – FCAV – UNESP, as quais foram geradoras dessa aprendizagem. Analisamos as representações de agricultura e natureza desses estudantes geradas e suas inter-relações com a realização dessas visitas e a prática da educação ambiental. O diálogo e a reflexão sobre a importância de atividades dessa natureza – capazes de aproximar a universidade e a comunidade – fizeram com que os integrantes desse projeto de extensão percebessem a possível articulação entre o ensino, a pesquisa e a extensão. Essa experiência se insere no projeto de extensão “Educação Ambiental, Agricultura e Segurança Alimentar na Educação Básica” (Projeto Cultivaeco) que tem o apoio da Proex desde 2009, com a obtenção de recursos e bolsas.
Keywords: Environmental education; Agriculture; Educação ambiental; Agricultura